Growth rates and testicular characteristics of Ethiopian highland sheep offered chickpea haulm supplemented with incremental levels of Leucaena leucocephala leaf hay - Dana, N.; Shenkoru, T.; Tegegne, Azage (Elsevier, 2000)
A study was conducted to evaluate the effect of supplementing levels of Leucaena leucocephala leaves on reproductive capacity and growth of male highland sheep (Arsi type) in Debre Zeit Research Centre. Animals were randomly allotted to one of five experimental rations. In treatment 1 (NS) animals were allowed to feed only on chickpea haulm. Treatments 2 (L100), 3 (L200) and 4 (L300) consisted of 100, 200 and 300 g/head per day of sun dried leucaena leaf hay, while animals in treatment 5 (C300) received 300 g/head per day of concentrate mixture. The basal diet, chickpea haulm, was offered ad libitum to all groups. Leucaena supplementation significantly increased total DM intake without marked effect on intake of the basal diet. Live weight of sheep was found to have increased by 68, 88, 94 and 74 percent as a result of supplementation of 100, 200 and 300 g/head per day of sun dried leucaena leaves and 300 g/head/day of concentrate mixture, respectively. Epididymal growth was retarded in animals maintained solely on chickpea haulm and improved with supplementation. Similar effects were noted in all the epididymal components of both the left and right testes. The scrotal circumference of non-supplemented sheep has been reduced by about 10 percent while addition of leucaena to the diet increased testicular size by 20-24 percent. The diameters of the left and right testes were also affected positive by supplementation. It was concluded that supplementation of up to 300 g/head per day of leucaena leaf hay improved body weight gain of sheep with concurrent increases in testicular and epididymal sizes without resulting in clinical symptoms of toxicity.